Vertically Coupled Partially Tapered Ridge Waveguide Semiconductor FP Laser With Improved Divergence Angles - Mingwen Lan; Xun Li (IEEE Photonics Journal)
In this work, we present a semiconductor FP laser design with significantly reduced divergence angles particularly in the vertical direction. The laser has a pair of vertically stacked, propagation constant unmatched twin waveguides that is coupled by a tapered ridge at the output end. As such, the laser has a significantly extended mode profile at the output section while the light propagation in the main section is not affected. Our simulation result shows that the divergence angles can be reduced to 13° $ × $ 14° (horizontal $ × $ vertical), as opposed to typical values of 20° $ × $ 29° in conventional ridge waveguide laser structures without a sport size convertor integrated. This design does not need any regrowth, with no appreciable penalty brought to other laser characteristics either.